Hybrid mediator panel: A legal pluralism framework for resolving medical disputes under the Indonesian health law - Repelita Witri; Melita Widyastuti; Nanang Zuli Purwanto; Marsudi Dedi Putra; Carolina Kuntardjo (Institute of Computer Science (IOCS), 2026)
Background The transformation of medical-legal relationships from a paternalistic to a contractual model in Indonesia has triggered complex disputes that conventional, legalistic mechanisms often fail to resolve fairly. While Law No. 17 of 2023 mandates non-litigation resolution, the current mediation framework remains trapped in a state-centric paradigm that marginalizes professional ethics and social norms. Research Gap A critical research gap exists in the prevailing legal monism approach, which creates a